Inhibition of heat shock protein 90 rescues glucocorticoid-induced bone loss through enhancing bone formation. Issue 171 (July 2017) - Chen, Haixiao; Xing, Ji; Hu, Xinhua; Chen, Lihua; Lv, Haiyan; Xu, Chengyun; Hong, Dun; Wu, Ximei
Highlights: Inhibition of HSP90 attenuates glucocorticoid receptor transactivity. Inhibition of HSP90 enhances the osteoblastogenesis. Inhibition of HSP90 attenuates glucocorticoid-induced osteoblastogenesis. Systemic inhibition of HSP90 increases bone masses. Systemic inhibition of HSP90 reverses glucocorticoid-induced bone loss. Abstract: Endogenous glucocorticoids (GCs) support normal bone development and bone mass maintenance, whereas long-term exposure to pharmacological dosages of GCs uncouples bone formation and resorption, resulting in GC-induced osteoporosis (GIOP). Heat shock protein 90 (HSP90) chaperoning glucocorticoid receptor (GR) signaling prompts us to speculate that HSP90 plays critical roles in GC-mediated bone formation and GIOP. In the present study, inhibition of HSP90 activity by 17-Demethoxy-17-allyaminogeldanmycin (17-AAG) or knockdown of HSP90 expression by siRNAs attenuated dexamethasone(Dex)-induced GR nuclear accumulation and transcriptional output of GR signaling, whereas overexpression of HSP90α or HSP90β enhanced GR transactivity in C3H10T1/2 cells. Though 17-AAG itself enhanced osteoblastic differentiation, it restored the Dex(10 −8 M)-induced and Dex(10 −6 M)-negated osteoblastic differentiation in C3H10T1/2 cells and primary calvarial osteoblasts. Moreover, systemic administration of 17-AAG to mice induced not only osteoclastogenesis but also osteoblastogenesis, whereas bone formation possibly exceeded bone resorption, eventually leading to the increased bone masses. Likewise, systemic administration of 17-AAG to mice restored GC-negated osteoblastogenesis and enhanced GC-induced osteoclastogenesis, similarly, 17-AAG-induced bone formation possibly exceeded both 17-AAG- and GC-induced bone resorption, eventually resulting in rescue of GIOP. Together, the present study has revealed that inhibition of HSP90 restores GIOP through enhancing bone formation, and our findings may help to shed light on the pathogenesis of GIOP and provide targets for the therapeutic intervention of the disease.